FATIGUE AND FAULTY POSTURE CONNECTION AMONG CHILDREN, DIAGNOSED WITH DYSARTHRIA - Andrejeva Julija; Mockiene Asta; Zukauskiene Milda (Kharkov National Pedagogical University, 2015)
Purpose : To analyze spastic dysarthria form in children population dependency of fatigue and faulty posture relationship. Methods: Research performed with the permission of the bioethics committee (RE-BK-063). The Dutch Fatigue Scale (DUFS). Posture in standing was assessed by Hoeger and Kendall. Research subjects n=40. n=20 children diagnosed with spastic dysarthria and n=20 of children without dysarthria. Their age was 10±2.1years. Boys were n=20 and girls - n=20.Results were statistically significant at p<0.05. Microsoft Office 2013, Excel package were used to count a research results. Results: For children with dysarthria fatigue level is more significant that for children without dysarthria; results were statistically significant, p<0.05. Posture disorder for children with dysarthria was statistically significant higher than among children without dysarthria, p<0.05. Conclusions: For children with dysarthria fatigue level is higher than for healthy children, thus for the girls fatigue level is higher than for the boys. Spastic form dysarthria has an impact to a child posture, by creating a direct dependency between posture deformation and skeletal muscle system disease, which decreases muscle power and increasing fatigue for a child. To correct faulty posture thus to decrease fatigue the tight collaboration needed between rehabilitation team members.